SCASI Review and Planning Workshop Report - Abdulkadir, Birhan; Tadesse, Desalegn; Menamo, Sahlemariam; Mohammed, Edries; Abdu Mohammed; Teshome, Mindaye; Dabessa, Alemayehu; Mnalku, Abere; Regassa, Dereje (CIMMYT, 2025)
The SCASI Review and Planning Workshop, held on June 24 and25, 2025, at the ILRI Campus in Addis Ababa, served as a crucial strategic forum to critically assess the progress of the Scaling Conservation Agriculture-based Sustainable Intensification in Ethiopia (SCASI) initiative since 2022. Organized by CIMMYT and CFGB, the event brought together 41 diverse stakeholders, including government bodies, implementing partners, and donor representatives, with the objective of consolidating key lessons, reviewing bottlenecks, and collaboratively developing actionable plans for the remainder of 2025. This multi-stakeholder engagement successfully validated the project's performance and renewed the shared commitment essential for sustained scaling efforts. The project review confirmed SCASI's high success and relevance. The Endline Impact Assessment revealed that CASI practices achieved an exceptional 87.5% adoption rate and resulted in significant productivity gains, most notably a maize yield increase of up to 67.7%. While this impact validates the CASI package as a highly effective response to soil and climate challenges, the review also identified critical limitations. Results for wheat and teff were not significant, signaling the need for further package optimization. More urgently, two major sustainability threats were highlighted: high government staff turnover, which risks institutional memory, and the cost and scarcity of inputs, which makes scaling financially challenging. The resulting action plan focuses on immediate institutional transition to secure long-term gains. The strategy prioritizes embedding CASI within formal government extension systems and utilizing local by-laws to secure ownership and mitigate staff turnover. To directly counteract high input costs, the plan promotes low-cost, local alternatives (vermicomposting, green manure, cover crops). Finally, the plan calls for a re-analysis of impact data for strategic refinement and utilizing mass media, farmer-to-farmer training, and a central CASI knowledge hub to actively integrate lessons into the national agricultural extension system.